Corporate Governance Effectiveness: A Sectoral Comparison of the Indian Economy - Soni, Ashish; Agarwal, Nitisha; Kumari, Pritam (Indian Journal of Research in Capital Markets, 2015)
Stock price crash is a phenomenon that usually occurs due to the presence of bubbles in the stock prices, and this problem arises due to sub-optimal management practices such as tax evasion, working on projects with negative present value, and lack of transparency of financial information. Research studies in the field of crash risk suggest that effective corporate governance mechanisms can curb sub-optimal managerial decision-making. This suggests that the rate of stock price crash can be used as a measure of effectiveness of the corporate governance mechanisms within a company. This research explored and analyzed the effectiveness of the corporate governance mechanism in different sectors of the Indian economy using a sample of 55 companies listed on the Bombay Stock Exchange. The study used daily stock price data of these companies during the period from FY2004-05 to FY2013-14. The research findings showed that among all the sectors of the Indian economy, the auto sector, metal & mining sector, and IT sector showed higher levels of corporate governance effectiveness.